Cenozoic Rotation History of Borneo and Sundaland, SE Asia Revealed by Paleomagnetism, Seismic Tomography, and Kinematic Reconstruction. Issue 8 (12th August 2018) - Advokaat, Eldert L.; Marshall, Nathan T.; Li, Shihu; Spakman, Wim; Krijgsman, Wout; van Hinsbergen, Douwe J. J.
Abstract: SE Asia comprises a heterogeneous assemblage of fragments derived from Cathaysia (Eurasia) in the north and Gondwana in the south, separated by suture zones representing closed former ocean basins. The western part of the region comprises Sundaland, which was formed by Late Permian‐Triassic amalgamation of continental and arc fragments now found in Indochina, the Thai Penisula, Peninsular Malaysia, and Sumatra. On Borneo, the Kuching Zone formed the eastern margin of Sundaland since the Triassic. To the SE of the Kuching Zone, the Gondwana‐derived continental fragments of SW Borneo and East Kalimantan accreted in the Cretaceous. South China‐derived fragments accreted to north of the Kuching Zone in the Miocene. Deciphering this complex geodynamic history of SE Asia requires restoration of its deformation history, but quantitative constraints are often sparse. Paleomagnetism may provide such constraints. Previous paleomagnetic studies demonstrated that Sundaland and fragments in Borneo underwent vertical axis rotations since the Cretaceous. We provide new paleomagnetic data from Eocene‐Miocene sedimentary rocks in the Kutai Basin, east Borneo, and critically reevaluate the published database, omitting sites that do not pass widely used, up‐to‐date reliability criteria. We use the resulting database to develop an updated kinematic restoration. We test the regional or local nature of paleomagnetic rotations against fits between the restored orientation of the Sunda Trench and seismic tomography images of the associated slabs. Paleomagnetic data and mantle tomography of the Sunda slab indicate that Sundaland did not experience significant vertical axis rotations since the Late Jurassic. Paleomagnetic data show that Borneo underwent a 35° counterclockwise rotation constrained to the Late Eocene and an additional 10° counterclockwise rotation since the Early Miocene. How this rotation was accommodated relative to Sundaland is enigmatic but likely involved distributed extension in the West Java Sea between Borneo and Sumatra. This Late Eocene‐Early Oligocene rotation is contemporaneous with and may have been driven by a marked change in motion of Australia relative to Eurasia, from eastward to northward, which also has led to the initiation of subduction along the eastern Sunda trench and the proto‐South China Sea to the south and north of Borneo, respectively. Key Points: We present new paleomagnetic data from Eocene‐Miocene sedimentary rocks in Kutai Basin, Borneo, and compile all available paleomagnetic data from Mesozoic and Cenozoic rocks in Sundaland and Borneo We compare reconstructed trenches with seismic tomography to evaluate the regional or local nature of paleomagnetic results We provide a kinematic restoration of Borneo and Sundaland since the Eocene that is consistent with paleomagnetism and tomography